Membangun Identitas Lokal: Strategi Komunikasi Pemasaran dan Pembentukan Citra Merek Kedai Kopi’ah di Indonesia - Armidya, Sheftyan Dwi; Lestaluhu, Said (Universitas Pattimura, 2025)
This study aims to examine the strategic marketing communication employed in building local identity and brand image at Kedai Kopi’ah in Eastern Indonesia, specifically in Ambon City, Maluku. The main focus is on how Kedai Kopi’ah designs and implements effective communication approaches to strengthen consumer attachment to local values while differentiating itself from competitors in an increasingly competitive coffee shop industry. A descriptive qualitative method was utilized, incorporating field observations, in-depth interviews with management and customers, and documentation of marketing activities. The findings reveal that Kedai Kopi’ah successfully established its brand image through the stages of the AIDA (Attention, Interest, Desire, Action) communication model. The process begins by capturing consumer attention through local symbols, followed by fostering interest and desire via cultural narratives, and culminating in actions such as customer visits and loyalty. These findings suggest that integrating local values into marketing communication strategies not only enhances brand identity but also improves the competitiveness of local businesses. The novelty of this research lies in its exploration of local wisdom-based marketing approaches as a strategic instrument for brand image development in Eastern Indonesia, a region that has been underrepresented in marketing studies. This study recommends further development of culturally grounded marketing communication models as a significant contribution to the advancement of social sciences and humanities, particularly within marketing and cultural communication studies.